Analysis of entropy generation and biomechanical investigation of MHD Jeffery fluid through a vertical non-uniform channel. (December 2021) - Vaidya, H.; Rajashekhar, C.; Manjunatha, G.; Wakif, A.; Prasad, K.V.; Animasaun, I.L.; Shivaraya, K.
Abstract: Homogenous and heterogeneous reactions play an essential role in combustion, polymer production, ceramic production, distillation, catalysis, and biochemical procedures. Haemoglobin molecules are magnetic from a biochemical perspective. The existence of magnetic resonance imaging (MRI) and electrical gadgets with an electromagnetic field allows explaining the essential functions of living species. Inspired by these ideas, the current research project aims to investigate the influence of homogeneous and heterogeneous responses on the peristaltic flow of MHD Jeffrey fluid. The geometry consists of a non-uniform vertical channel when subjected to velocity slip and temperature slip conditions. The solution treatment involves the perturbation series analysis strategy for solving the governing partial differential equations. Entropy generation analyses have been carried out. The consequences of velocity, temperature, skin friction, Nusselt number, pressure rise versus mean circulation, trapping phenomena, homogenous, and heterogeneous reaction are assessed for major restraints getting in the problem with the help of graphs. Furthermore, the entropy generation which plays a vital role in understanding numerous biological processes. Therefore, the present study has a potential application in industry and medicine. Graphical abstract: Image 1